Paired t-Test to Determine the Effect of Snowball Throwing on Student Learning Outcomes - Wardani, Dian Kusuma; Nisa', Khoirun; Aisyah, Ani Nur (The Future of Education Journal, 2025)
Snowball Throwing is a learning activity in which student use snowballs or ball-shaped paper as a tool or medium to build student knowledge by utilizing various learning resources. This study aims to determine the effect of using this learning model on learning outcomes using the Snowball Throwing learing model at SMPN 2 Sumobito. The method used in this study was an experimental method. The instrument used was multiple-choice questions to determine student learning outcomes. The subjects used in this study were grade VIII G students at SMPN 2 Sumobito. The results of this study indicate that the Snowball Throwing learning model has an effect on the learning of grade VIII students in Islamic Religious Education (PAI) at SMPN 2 Sumobito. This can be proven by the results of the hypotesis test using a t-test with a significance level of (0,019) < (0,05), thus rejecting H0. Therefore, the snowball throwing learing model has an impact on student learning outcomes. Therefore, this learning model can be used as an alternative learning model for teachers to maximeze student learning outcomes, particulary in Islamic Religious Education (PAI).